O ciclo de substrato da creatina e a origem do lipídio no tecido adiposo inguinal de ratos recém desmamados, submetidos a dieta hipoproteica-hiperglicídica por 15 dias - Allebrandt Neto, Edgar Willibaldo (2022)
The low-protein, high-carbohydrate (LPHC) diet administered to growing rats soonafterweaning, for 15 days, promoted an increase in energy expenditure by uncoupling protein1(UCP1)in interscapular brown adipose tissue (iBAT), and also due to the occurrence of the browningprocessin the perirenal white adipose tissue (periWAT). However, we believe that inguinal whiteadiposetissue (ingWAT) may also contribute to energy expenditure through other mechanisms, independentof UCP1. Therefore, the aim of this work is to investigate the presence of the creatine-drivensubstrate cycle, and the origin of lipids in ingWAT, since that tissue showed an increase inthelipidscontent in rats submitted to the LPHC diet for 15 days. We observed increases of 45%and154%increatine kinase and alkaline phosphatase activity in ingWAT, respectively, of the LPHCanimals.The mitochondrial NADH/NAD+ ratio is lower (11.30%) in ingWAT of LPHC animals. IntheLPHCanimals treated with β-guanidinopropionic, the extracellular uptake of creatine in ingWATwaslower,as was the rectal temperature. Regarding lipid metabolism, we observed that in ingWAT, thealipolysis in vitro when stimulated with noradrenaline (10 -6 mol.L -1) is lower, and therewerenochanges in baseline levels. Increases in the activity of enzymes were also observed: malic(245%),glucose-6-phosphate dehydrogenase (62.16 %), and ATP-citrate lyase (48%), in additiontoanincrease in the PPARγ content (48.73%) of LPHC animals. The results showthe occurrenceofthecreatine-driven substrate cycle in ingWAT, and that the increase in the relative mass maybeduetoan increase in de novo fatty-acid synthesis.